Vulnerabilidade de famílias de agricultores convivendo com hexaclorociclohexano - BHC : um desafio para o cuidado à saúde - Buriola, Aline Aparecida (2009)
To argue the risks to the health and the environment and the exposition of the population the highly toxic products, mainly the illegal passengers as the hexaclorociclohexano - BHC is necessary to evaluate aspects that surpass the question of the safe behavior, style of life and education in health. Considering that the vulnerability concept can contribute for this understanding, the present study it has as objective to argue the vulnerability of families of agricultural agriculturists who coexist BHC stored in its properties. One is about a exploratório descriptive study, using the theoretical referencial of the vulnerability, the method of situacional diagnosis fast e visits to domiciliate as resources for the empirical study. Effectively 27 families had been investigated, residents in pertaining cities to the Regional Nucleus of Agriculture of Maringá - PR. You argue the risks you the health and the environment and the exposition of the population the highly toxic products, mainly the illegal passengers the hexaclorociclohexano - BHC is necessary you evaluate aspects that surpass the question of the disembarasses behavior, style of life and education in health. Considering that the vulnerability concept can contribute will be this understanding, the present study it has objective you argue the vulnerability of families of agricultural agriculturists who coexist BHC stored in its properties. One is about the exploratório descriptive study, using the theoretical referencial of the vulnerability, the method of situacional diagnosis fast and visits you domiciliate resources will be the empirical study. Effectively 27 families had been investigated, residents in pertaining cities you the Regional Nucleus of Agriculture of Maringá - PR. The majority of the families informed to have knowledge on the prohibition of the BHC, but few had known to justify the reasons for this prohibition. The main place of storage of the BHC is tulhas or abandoned houses, with amounts between one and 1000 kg conditioned, mainly, in bags of paper or not complete plastics and tambores of polyethylene. Two families had still related to use the BHC "to kill insects". The individual vulnerability this related with the presence of masculine heads of family with low escolaridade, some with age above of 60 years, greater number of members gifts in the constitution of these families, families inhabiting in the property more than has ten years, and use of the BHC "to kill insects". The social vulnerability presents as component facilitadores the familiar low income, the television as source of information, and difficulty presented for the family in taking possetion itself of decisions that can change its reality. The programmatical vulnerability is increasing due to absence of information and resolutive actions of the agencies of Agriculture for the solution of the present BHC in the country properties. To argue the vulnerability of the families of agricultural agriculturists who have in its properties the BHC stored is not a simple task, being essential the faithful comprometimento to the causes of the populations most vulnerable, in order to materialize the objectives of attention and care to the health ambient human being and promised to all population.